2022
DOI: 10.1039/d2bm00634k
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized self-assembling peptide RADKPS hydrogels promote regenerative repair of degenerated intervertebral discs

Abstract: Objective: The aim of this study was to investigate whether the functionalized self-assembling peptide hydrogel RADKPS is safe and effective for regenerative repair of degenerative intervertebral discs.Methods: An in vitro...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Further cell delivery optimization may be required to achieve substantial disc height or water content improvement following treatment. For example, combining microscaffolds with an additional hydrogel system like fibrin-genipin, self-assembling peptide, or PNIPAM , as a continuous medium could help increase IVD height and restore NP biomechanical properties . However, conducting clinical trials with novel biomaterials is a highly regulated and resource-intensive process.…”
Section: Resultsmentioning
confidence: 99%
“…Further cell delivery optimization may be required to achieve substantial disc height or water content improvement following treatment. For example, combining microscaffolds with an additional hydrogel system like fibrin-genipin, self-assembling peptide, or PNIPAM , as a continuous medium could help increase IVD height and restore NP biomechanical properties . However, conducting clinical trials with novel biomaterials is a highly regulated and resource-intensive process.…”
Section: Resultsmentioning
confidence: 99%
“…As well‐documented, small‐sized nanoparticles generally exhibit relatively high accumulation in the kidneys. [ 29 ]…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the utilization of bioactive peptides for the regulation of IVD cells and enhancement of IDD processes has garnered growing interest in recent times. Tang et al (2022) delivered three short peptide fragments, SNVI, KPSS, and KAIS, which have the biological activity of bone morphogenetic protein-7. They found that KPSS exhibited the most potent biological activity and most extended duration of action.…”
Section: Therapeutic Factorsmentioning
confidence: 99%
“… Ligorio et al (2021) used a self-assembled peptide FEFKFEFK (F: phenylalanine; K: lysine; E: glutamic acid) to construct a hydrogel and tried to treat IDD with GO-loaded TGF-β3, clearly indicating that GO reinforces the mechanical structure of self-assembled peptides and enables TGF-β3 slowly release. In another study, Tang et al (2022) used self-assembled peptides as hydrogel substrates and directly modified bioactive polypeptide fragments on self-assembled peptides.…”
Section: Delivery Platforms For Therapeutic Factorsmentioning
confidence: 99%